Eksplorasi Potensi Pembelajaran Berbasis Kompetensi Untuk Persiapan Karier Siswa Di Era Digital - Lasino Lasino (Pusat Riset dan Inovasi Nasional, 2021)
Competency-based learning has emerged as a progressive and dynamic educational paradigm, which will change the way we view education. Rapid technological advances and increasingly changing future demands require education and educators to be active. In this case, CBL offers the right response, where this innovative approach prioritizes the mastery of students' special skills and knowledge, not only about in-depth understanding of subjects and the acquisition of practical skills, but also preparing students' careers in facing the future era that requires many skills and abilities. needs to be grown from the start to continue to be developed.